Abrogated cryptic activation of lentiviral transfer vectors - Luche, Ralf M. (Nature Publishing Group, 2012)
Despite significant improvements in lentivirus (LV) vector-based gene therapy there are still several safety risks using LV vectors including the potential formation of replication-competent LV particles. To address this shortcoming, we constructed a novel and safer gene transfer system using modified SIN-based LV gene transfer vectors. Central to our approach is a conditional deletion of the Ψ packaging signal after integration in the target genome. Here we demonstrate that after transduction of target cells, conventional SIN-based LV transfer vectors can still be mobilized. However mobilization is rendered undetectable if transductions are followed by a Cre/loxP-mediated excision of Ψ. Thus conditional elimination of the packaging signal may represent another advance in increasing the safety of LV vectors for gene therapeutic treatment of chronic diseases.